The Concept of Imam Ibn Al-Jauzi's Independent Education in the Book of Laftatu Al-Kabid Ila Nashihati Al-Walad - Ibnu Jarir Dainuri; Rahmat Rosyadi; Santi Lisnawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Building a teacher's personality that includes spiritual and religious values is very important and fundamental, because he is responsible for the quality of education, he is the heir of the Prophet, he is an agent of improvement (ishlahul ummah) and the teacher is the front guard in realizing the ideals of independence. This research aims to analyze the concept of Ibn al-Jauzi's Independent Education in the book Lafitatu al-kabid ila nashihati al-walad. This research is a type of qualitative research with two methods, namely library research (library research). The primary data source for this research is the book Lafitatu al-kabid ila nashihati al-walad and secondary data as well as other supporting books. The result of research on the book Lafitatu al-kabid ila nashihati al-walad is that Independent Education (tarbiyah dzatiayah ) is a continuous educational effort carried out by individuals in educating themselves to increase their own capacity in various areas of life, by applying various means prescribed by Islam. There are a minimum of 6 (six) aspects of Independent Education, namely: 1). Piety Aspect 2). Worship Aspect 3). Moral Aspect 4). Fikriyah Aspect 5). Da'wah aspects and 6). Ruhiyah Aspect.